1995
DOI: 10.1001/archpsyc.1995.03950160008002
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression for Glutamic Acid Decarboxylase Is Reduced Without Loss of Neurons in Prefrontal Cortex of Schizophrenics

Abstract: The prefrontal cortex of schizophrenics shows reduced expression for GAD in the absence of significant cell loss. This may be brought about by an activity-dependent down-regulation associated with the functional hypoactivity of the DLPFC. The lack of significant alterations in cell numbers in the DLPFC and frontal lobe volume in schizophrenics also implies that overall cortical neuronal migration had not been compromised in development. Previous reports of altered neuronal distribution in the subcortical white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
573
6
5

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(622 citation statements)
references
References 49 publications
38
573
6
5
Order By: Relevance
“…Activation of both prefrontal cortical interneurons and pyramidal cells is consistent with the actions of atypical APDs such as clozapine (Deutch and Duman, 1996). This is particularly interesting because the number and/or function of GABA interneurons in the PFC may be compromised in schizophrenia (Hashimoto et al, 2003;Benes et al, 2000;Lewis et al, 1999;Akbarian et al, 1995). Our data suggest that NT agonists activate PFC interneurons and could thereby compensate for a prefrontal cortical GABAergic deficit in schizophrenia.…”
Section: Discussionsupporting
confidence: 70%
“…Activation of both prefrontal cortical interneurons and pyramidal cells is consistent with the actions of atypical APDs such as clozapine (Deutch and Duman, 1996). This is particularly interesting because the number and/or function of GABA interneurons in the PFC may be compromised in schizophrenia (Hashimoto et al, 2003;Benes et al, 2000;Lewis et al, 1999;Akbarian et al, 1995). Our data suggest that NT agonists activate PFC interneurons and could thereby compensate for a prefrontal cortical GABAergic deficit in schizophrenia.…”
Section: Discussionsupporting
confidence: 70%
“…Our recent unpublished observations also reveal a reduction in the density of CB-IR interneurons in dlPFC of subjects with schizophrenia (Rajkowska et al, 2002). Moreover, reductions in immunoreactivity for glutamic acid decarboxylase (GAD65) (the GABA synthesizing enzyme; Benes et al, 2000), mRNA for GAD (Akbarian et al, 1995;Hashimoto and Lewis, 2006;Hashimoto et al, 2003;Volk et al, 2000), and the GABA membrane transporter, GAT-1 (Pierri et al, 1999;Woo et al, 1998) have been observed in dlPFC and anterior cingulate cortex in manic-depressive disorder and schizophrenia. Whether similar reductions in GAD or GAT-1 mRNA and protein are present in our cohort of depressed subjects is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the size of specific populations of cortical GABAergic synapses (Woo et al 1998) and of glutamic acid decarboxylase expression (Akbarian et al 1995;Impagnatiello et al 1998) and an increase in the number of GABA A receptors in cortical regions (Benes et al 1992;Benes et al 1996), suggestive of a reduced GABAergic tone, have been observed in post-mortem brain specimens obtained from individuals with schizophrenia. Moreover, it has been shown that long-term treatment with neuroleptics increases GABA-immunoreactive terminals in rodent medial prefrontal cortex (Vincent et al 1994) and elicits a dose-related increase of glutamic acid decarboxylase expression in hippocampus of schizophrenic patients (Todtenkopf and Benes 1998).…”
Section: Discussionmentioning
confidence: 99%